2023
DOI: 10.1007/s00382-023-06833-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in atmospheric moisture transport over tropical South America: an analysis under a climate change scenario

Abstract: Warming induced by increased greenhouse gas emissions is intensifying the global water cycle and increasing the water vapor content of the global atmosphere. However, there is a lack of scientific literature assessing how regional atmospheric moisture transport and recycling will change in a warming climate. This work analyzes the projections of atmospheric moisture transport and recycling over tropical South America by the end of the twenty-first century (2070–2100) under a climate change scenario (RCP8.5). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 127 publications
0
0
0
Order By: Relevance
“…For the Amazon as a whole, the effects of deforestation on moisture recycling seem to be overshadowed by those of increasing atmospheric CO2 concentrations, although in terms of recycling ratios, the larger deforestation in SSP3-7.0 compensates for the stronger radiative forcing in SSP5-8.5. This is consistent with results from CMIP5 models, where every 10% of the basin deforested leads to an average precipitation decline of only 1.6% (Spracklen 430 and Garcia-Carreras, 2015), and where severe climate change (RCP8.5) leads to increased moisture influx from the Atlantic into South America, but reduced precipitation (recycling) over the Amazon (Arias et al, 2023). The comparatively small effect of deforestation is further confirmed by experiments using a range of CMIP6 models, where one study found that warming, via atmospheric circulation changes, accounts for 55% of Amazon drying under SSP3-7.0 conditions.…”
Section: Regional Differencessupporting
confidence: 86%
“…For the Amazon as a whole, the effects of deforestation on moisture recycling seem to be overshadowed by those of increasing atmospheric CO2 concentrations, although in terms of recycling ratios, the larger deforestation in SSP3-7.0 compensates for the stronger radiative forcing in SSP5-8.5. This is consistent with results from CMIP5 models, where every 10% of the basin deforested leads to an average precipitation decline of only 1.6% (Spracklen 430 and Garcia-Carreras, 2015), and where severe climate change (RCP8.5) leads to increased moisture influx from the Atlantic into South America, but reduced precipitation (recycling) over the Amazon (Arias et al, 2023). The comparatively small effect of deforestation is further confirmed by experiments using a range of CMIP6 models, where one study found that warming, via atmospheric circulation changes, accounts for 55% of Amazon drying under SSP3-7.0 conditions.…”
Section: Regional Differencessupporting
confidence: 86%
“…This result agrees with the projections of reductions higher than 35% reported by Brêda et al (2020) for northern South America based on CMIP5 GCMs. Those reductions of almost half of the precipitation around the year in the region, also reported by Arias et al (2023), added to the ongoing trend of deforestation in the Guianese rainforest, could enhance the severity of droughts in the basin (Sorí et al, 2023) and accelerate the savannisation of the region (Valencia et al, 2023). These alterations could lead to a reduction of the water vapor flux from the Atlantic Ocean towards the Amazon basin (Nieto et al, 2008;Bovolo et al, 2018) that transit through the Orinoco River basin; a reduction of the outflow of precipitation from the Orinoco basin towards Northern South America via moisture recycling (Hoyos et al, 2018;Escobar et al, 2022); extreme precipitation events (Martínez et al, 2023), or even the role of Central America as an evaporative source (Durán-Quesada et al, 2017).…”
Section: Discussionsupporting
confidence: 62%
“…However, they did not differentiate among different SSPs. Baker & Spracklen (2022) and Arias et al (2023) used Earth System Models to study changes in moisture recycling for particular 530 regions.…”
Section: Limitationsmentioning
confidence: 99%